(untitled) (Revista Rupturas, 2025)
This article reflects on inclusivity in university music schools Objective: It aims to highlight the problem of discrimination in the competition process for auditions for the admission to bachelor’s and bachelor’s degree programs in music education. Method: The experience of a teacher and a 38-year-old student, who enters the Pre-University Program of the School of Musical Arts of the University of Costa Rica with little previous knowledge of formal music theory, is used. Results: The results show positive feedback for both the student and the teacher, demystifying various myths about the subject. Conclusions: It is concluded that many popular music professionals have not had access to obtaining an academic degree